Comparative review of piezoelectric biomaterials approach for bone tissue engineering. Issue 12 (13th August 2022) - Samadi, Ali; Salati, Mohammad Amin; Safari, Amin; Jouyandeh, Maryam; Barani, Mahmood; Singh Chauhan, Narendra Pal; Golab, Elias Ghaleh; Zarrintaj, Payam; Kar, Saptarshi; Seidi, Farzad; Hejna, Aleksander; Saeb, Mohammad Reza
Abstract: Bone as a minerals' reservoir and rigid tissue of the body generating red and white blood cells supports various organs. Although the self-regeneration property of bone, it cannot regenerate spontaneously in severe damages and still remains as a challenging issue. Tissue engineering offers several techniques for regenerating damaged bones, where various biomaterials are examined to fabricate scaffolds for bone repair. Piezoelectric characteristic plays a crucial role in repairing and regenerating damaged bone by mimicking the bone niche behavior. Piezoelectric biomaterials show significant potential for bone tissue engineering. Herein we try to have a comparative review on piezoelectric and non-piezoelectric biomaterials used in bone tissue engineering, classified them, and discussed their effects on implanted cells and manufacturing techniques. Especially, Polyvinylidene fluoride (PVDF) and its composites are the most practically used piezoelectric biomaterials for bone regeneration. PVDF and its composites have been summarized and discussed to repair damaged bone tissues.